Comparative in vivo evaluation of three types of honey on topical wound healing activity in rabbits - Nagiat T Hwisa, Prakash Katakam, Babu Rao Chandu, Einas Ghafar Abadi and Ebtihal Mosbah Shefha (Journal of Applied Pharmaceutical Science, 2013)
The present investigation has focused on the comparative evaluation of topical wound healing activity in rabbits using three types of honeys such as Sidr (SDH), Thyme (TYH), Spring (SPH). The activity was compared with commercial wound healing formulations, Mebo (MBC) and Fusidin (FSC) creams. Among the different types of the honey SDH was found to possess higher healing rate of wounds induced either by thermal or chemical methods. Whereas, in thermal induced burns, both TYH and SPH have shown similar wound healing activity but better than that of standard drugs. The activity for thermal and chemical induced burns was found in the order of SDH > TYH/SPH > MBC > control and SDH > TYH > SPH > FSC > control respectively. Among the three tested honeys, the t-test data was compared to those of controls and it was found that there was a significant (p
Keywords: Honey, Sidr, Thyme, Spring, wound healing, topical.&